تطوير شمال غرب نابلس لمنطقة إقتصادية نموذجية - سماعنة, ريمه يوسف (My University, 2017)
The concept of local economic development is one of the concepts that should be emphasized in our Palestinian reality because of the occupation and its control over most of the natural and cultural resources that can be a source of support for the local economy as well as the competition of Israeli products for Palestinian products which negatively affects the local economy. To preserve the resources and marketing of Palestinian products and provide employment opportunities for young workers working in the occupied home and drain their capabilities. The local economic development project aims to preserve the land and protect it from settlement and enable the communities to optimize the use of available resources and link the local authorities with a strategic plan to support each other and expand the economic base and job opportunities through devising strategic programs and projects to remove the stones and facilitate investment.